2015
DOI: 10.1016/j.ijcha.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented QRS and ejection fraction in heart failure patients admitted to the hospital

Abstract: BackgroundFragmented QRS (FQRS) in 12 lead ECG was recently correlated with various outcomes in ischemic and non-ischemic heart disease. We studied the relationship between FQRS and ejection fraction (EF) in heart failure patients with QRS < 120 ms.MethodsMedical records and echocardiograms of 339 patients admitted with CHF were reviewed. ECGs were read twice by a reader blinded to all data.Results70 patients with wide QRS were excluded; 63 patients had FQRS and 206 patients did not have FQRS. FQRS group were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…The impact of baseline QRSd on pre-to post-LVAD change in LVEF has not been previously studied in CHF patients undergoing LVAD implantation, although the relation between fragmented QRS and LVEF has been discussed in HF patients. 29 s Similarly, the impact of baseline QRSd on LVEDD before and after LVAD support in chronic HF patients has not been reported yet. A positive association between QRSd and LV size in patients with bundle branch block was discussed previously, 31,32 and it has been suggested that LV size does not modify the effect of baseline QRSd and its association with outcomes following cardiac resynchronization therapy.…”
Section: Discussionmentioning
confidence: 97%
“…The impact of baseline QRSd on pre-to post-LVAD change in LVEF has not been previously studied in CHF patients undergoing LVAD implantation, although the relation between fragmented QRS and LVEF has been discussed in HF patients. 29 s Similarly, the impact of baseline QRSd on LVEDD before and after LVAD support in chronic HF patients has not been reported yet. A positive association between QRSd and LV size in patients with bundle branch block was discussed previously, 31,32 and it has been suggested that LV size does not modify the effect of baseline QRSd and its association with outcomes following cardiac resynchronization therapy.…”
Section: Discussionmentioning
confidence: 97%
“…fQRS complex is frequently used as an ECG marker of myocardial fibrosis in various heart diseases and has a prognostic value 12–14 . The EF is lower in patients with fQRS 43–45 . Healthy subjects with fQRS who have a normal EF have regional LV systolic dysfunction as indicated by GLS 46 .…”
Section: Discussionmentioning
confidence: 99%
“…В группе с распространенной (≥ 2 локализаций) fQRS регистрировались более низкие значения ФВ ЛЖ в сравнении с группой без fQRS (p < 0,05). Однако, на наш взгляд, существенным ограничением вышеуказанной работы является включение участников с ХСН различной этиологии (ИБС, артериальная гипертензия, токсическая кардиомиопатия), что не позволяет объяснять полученные различия исключительно распространенностью рубцовых изменений миокарда [26].…”
Section: Fqrs -предиктор неблагоприятного течения ибсunclassified